2015
DOI: 10.1245/s10434-015-4477-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perioperative Red Blood Cell Transfusions on Long-Term Outcomes after Hepatectomy for Colorectal Liver Metastases

Abstract: Perioperative RBCT is independently associated with decreased OS and RFS following hepatectomy for CRLM. Interventions to minimize and rationalize the use of RBCT for hepatectomy are warranted to mitigate this detrimental effect on long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 34 publications
4
67
0
2
Order By: Relevance
“…Almost a third of the patients in the study did not have a malignancy. Although multiple studies examining associations between liver resection for malignancy and blood transfusions have demonstrated the adverse impact on oncologic outcomes when blood products are used [1721], few studies have established whether or not blood transfusion poses an additional risk for hepatectomy patients undergoing resection for a non-oncologic indication [1, 22]. In our study, transfusion use did not differ between patients undergoing resection for malignancy and non-malignant diagnoses.…”
Section: Discussionmentioning
confidence: 47%
“…Almost a third of the patients in the study did not have a malignancy. Although multiple studies examining associations between liver resection for malignancy and blood transfusions have demonstrated the adverse impact on oncologic outcomes when blood products are used [1721], few studies have established whether or not blood transfusion poses an additional risk for hepatectomy patients undergoing resection for a non-oncologic indication [1, 22]. In our study, transfusion use did not differ between patients undergoing resection for malignancy and non-malignant diagnoses.…”
Section: Discussionmentioning
confidence: 47%
“…All identified studies were observational design studies involving a total of 10621 patients. Seven studies were from USA [5, 7, 9, 16, 21, 22, 24], four from Italy [4, 8, 12, 13], three from Japan [3, 14, 18], two from UK [11, 25], two from Germany [20, 23], one from Sweden [2], one from France [6], one from Spain [10], one from Brazil [15], one from China [17], one from Canada [19], and one from the Netherlands [26]. The blood product transfusion rate was highly variable across studies ranging from 13.5% to 91.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies compared the characteristics of transfused patients versus those nontransfused patients [16, 1921]. Pooled analysis showed that transfusion was associated with female gender ( P <0.001), higher prevalent preoperative anemia ( P <0.001), more extended or major hepatectomy ( P <0.001), increased estimated blood loss ( P <0.001), and longer duration of surgery ( P <0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, blood loss remains a significant concern and has been the topic of numerous studies (3)(4)(5). As a result, red blood cell transfusions (RBCT) are required in up to 25% of patients undergoing liver resection (6)(7)(8). Thus, hepatectomy represents a unique challenge with regards to blood management strategies.…”
Section: Introductionmentioning
confidence: 99%